2018
DOI: 10.1042/bsr20181213
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of lncRNA snaR is correlated with postoperative distant recurrence of HPV-negative cervical squamous cell carcinoma

Abstract: Long non-coding RNAs (lncRNAs) snaR is a newly identified lncRNA with known functionality only in colon cancer. Our study was carried out to investigate the involvement of lncRNA snaR in human papillomaviruses (HPV)-negative cervical squamous cell carcinoma (CSCC). In the present study, plasma levels of lncRNA snaR in 108 patients with HPV-negative CSCC at stage I and II, and 35 healthy female controls were detected by real-time quantitative PCR. ROC curve analysis was performed to evaluate the diagnostic valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
1
4
0
Order By: Relevance
“…Long non-coding RNAs (lncRNAs, >200 nt) lack protein coding capacity but play pivotal roles in cancer biology by regulating gene expression [9]. A recent study reported an lncRNA named snaR is involved in the recurrence of HPV-negative but not HPV-positive cervical squamous cell carcinoma (CSCC, a major subtype of cervical cancer) [10], indicating the involvement of lncRNAs in HPV-negative CSCC. In a recent study, Lu et al reported a novel lncRNA SRA1 as a potential tumor suppressive lncRNA in hepatocellular carcinoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs, >200 nt) lack protein coding capacity but play pivotal roles in cancer biology by regulating gene expression [9]. A recent study reported an lncRNA named snaR is involved in the recurrence of HPV-negative but not HPV-positive cervical squamous cell carcinoma (CSCC, a major subtype of cervical cancer) [10], indicating the involvement of lncRNAs in HPV-negative CSCC. In a recent study, Lu et al reported a novel lncRNA SRA1 as a potential tumor suppressive lncRNA in hepatocellular carcinoma [11].…”
Section: Introductionmentioning
confidence: 99%
“…lncRNA CASC2a is identified as not only a prognosis biomarker but also a potential therapeutic target in the early recurrence of bladder cancer [20] . These data confirm the significance of ncRNAs in cancer recurrence [21] , [22] , [23] , [24] .…”
Section: Introductionsupporting
confidence: 80%
“…11 Some lncRNAs were significantly associated with CC recurrence, such as HOTAIR, snaR and MEG3. [12][13][14] LncRNAs provide new insights into the molecular mechanisms and treatments of cancer, and thus lay the ground work for the clinic.…”
Section: Introductionmentioning
confidence: 99%